EFFECT OF THERMAL ANNEALING ON PHASE TRANSFORMATIONS AND ORDERING OF THE MAGNETIC TEXTURE OF Fe3O4/Nd2O3 NANOCOMPOSITES (International Journal of Mathematics and Physics, 2022)
The paper presents the results of a study of the effect of thermal annealing on the phase transformations and subsequent ordering of the magnetic texture and superfine magnetic parameters in Fe3O4/Nd2O3 nanocomposites obtained by chemical deposition and subsequent mechanochemical synthesis. X-ray phase analysis and Mössbauer spectroscopy were used to characterize the properties of the obtained Fe3O4/Nd2O3 nanocomposites. Thermal annealing was carried out in an oxygen-containing medium in the temperature range of 400°C - 1000°C for 5 hours followed by cooling for 24 hours until reaching room temperature. The phase transformation dynamics of Fe2O3/NdFeO3 → NdFeO3 >>Fe2O3→ NdFeO3 type was established using X-ray phase analysis. According to the data of Mössbauer spectroscopy it was established that the domination of the NdFeO3 phase in the nanocomposite structure at annealing temperatures above 800°С leads to an ordering of the magnetic texture and an increase in the value of the superfine magnetic field to 502.8 kOe, approaching the values characteristic of the Fe2O3 structure (513 kOe).